2002
DOI: 10.1172/jci200214873
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen alters thresholds for B cell apoptosis and activation

Abstract: Estrogen is thought to contribute to the increased frequency of autoimmune disorders occurring in females, but a molecular basis for its effects on autoimmunity remains to be elucidated. We have shown previously that estrogen leads to the survival and activation of autoreactive cells in the naive repertoire. To identify the molecular pathways involved in B cell tolerance, we sought to identify genes that are differentially regulated by estrogen in mouse B cells. Several genes involved in B cell activation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 46 publications
2
124
1
Order By: Relevance
“…The association of the CYP17A1 )34CC genotype and Hap3 haplotype with increased risk of DLBCL in both men and women suggests a role for oestrogen and possibly other cholesterol metabolites formed via CYP17A1 in the pathogenesis of DLBCL. Oestrogen exerts pleiotropic effects on lymphocyte activation, proliferation, cell cycle progression and apoptosis, factors that may influence lymphoma risk (Grimaldi et al, 2002). In B-cells, oestrogen mediates its anti-apoptotic effects through upregulation of BCL-2.…”
Section: Resultsmentioning
confidence: 99%
“…The association of the CYP17A1 )34CC genotype and Hap3 haplotype with increased risk of DLBCL in both men and women suggests a role for oestrogen and possibly other cholesterol metabolites formed via CYP17A1 in the pathogenesis of DLBCL. Oestrogen exerts pleiotropic effects on lymphocyte activation, proliferation, cell cycle progression and apoptosis, factors that may influence lymphoma risk (Grimaldi et al, 2002). In B-cells, oestrogen mediates its anti-apoptotic effects through upregulation of BCL-2.…”
Section: Resultsmentioning
confidence: 99%
“…Medina and Kincade have shown convincingly that estrogen reduces B-cell lymphopoiesis during pregnancy [41]. Grimaldi et al [42] have reported on the effects of estrogen on B-cell activity. We reported that this reduction is reflected by week 34 when peripheral CD19?…”
Section: Is There a Systemic Immunosuppression During Pregnancy?mentioning
confidence: 98%
“…oestrogens also affect B-cell development by decreasing negative selection of naive immature B cells, enhancing the survival of autoreactive B cells 31 and enhancing polyclonal activation of B cells, which leads to higher serum levels of IgG and Igm (mediated by CD95-CD95L interactions 32 ). These B-cell effects might contribute to the increased incidence of many autoimmune diseases in women.…”
Section: Sex-based Differences In Immunity Oestrogen Influences Immunmentioning
confidence: 99%